Detection of mitochondrial DNA with 4977 bp deletion in leukocytes of patients with ischemic stroke - Huang, Yu-hua; Chen, Chiung-Mei; Lee, Yun-Shien; Chang, Kuo-Hsuan; Chen, Huei-Wen; Chen, Yi-Chun (PloS one, 2018)
Coronary artery disease is associated with a common mitochondrial DNA alteration, a 4977 bp deletion (mtDNA4977). The role of mtDNA4977 in ischemic stroke is unknown. Real-time quantitative PCR was performed to quantify total mtDNA and mtDNA4977 in leukocytes in 283 ischemic stroke cases and 135 controls. Ratios of mtDNA4977 to total-mtDNA and total-mtDNA to nuclear-DNA were calculated. Nested PCR and Sanger sequencing were used to confirm undetectable levels of mtDNA4977. For 191 patients and 74 control subjects in the male group and 92 patients and 61 control subjects in the female group, there were no significant between-group differences in age, cholesterol level, body mass index, stroke severity, or 4977 deletion. After adjusting for confounding factors, there was no correlation between mtDNA4977 amount and infarction risk, recurrent stroke, or stroke severity. However, mtDNA4977 was undetected in 6.94% subjects, and these individuals had a higher prevalence of stroke than those with detectable mtDNA4977 (OR: 0.181, 95% CI 0.041-0.798, p = 0.024). Additionally, mtDNA4977 status had no effect on stroke prognosis, including stroke severity and recurrent stroke. In conclusion, there was no apparent association between mtDNA4977 deletion and cerebral infarction. Undetectable mtDNA4977 may be a marker or risk factor for ischemic stroke.